2014
DOI: 10.1371/journal.pone.0091119
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Sensing Pathways in Human Embryonic Stem Cell Derived-Endothelial Cells: Role of NOD1 Receptors

Abstract: Human embryonic stem cell-derived endothelial cells (hESC-EC), as well as other stem cell derived endothelial cells, have a range of applications in cardiovascular research and disease treatment. Endothelial cells sense Gram-negative bacteria via the pattern recognition receptors (PRR) Toll-like receptor (TLR)-4 and nucleotide-binding oligomerisation domain-containing protein (NOD)-1. These pathways are important in terms of sensing infection, but TLR4 is also associated with vascular inflammation and atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
(46 reference statements)
3
14
0
Order By: Relevance
“…Similarly, endothelial cells from healthy donors released CXCL8 when stimulated with PAMPs directed at TLR2, 3, or 4, or with IL-1β. As with leukocytes in whole blood, endothelial cells from a cPLA 2 α-deficient patient released elevated levels of CXCL8 when stimulated with inflammatory agents, consistent with activation of NF-κB pathways following treatment with inflammatory stimuli, as we have previously described ( 25 ). Endothelial cells from either type of donor did not respond to ligands for TLR5, the pattern recognition receptor for motile bacteria and fungi, TLR7 and TLR8, pattern recognition receptors for single-stranded RNA viruses, or TLR9, which is the pattern recognition receptor for bacterial DNA.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, endothelial cells from healthy donors released CXCL8 when stimulated with PAMPs directed at TLR2, 3, or 4, or with IL-1β. As with leukocytes in whole blood, endothelial cells from a cPLA 2 α-deficient patient released elevated levels of CXCL8 when stimulated with inflammatory agents, consistent with activation of NF-κB pathways following treatment with inflammatory stimuli, as we have previously described ( 25 ). Endothelial cells from either type of donor did not respond to ligands for TLR5, the pattern recognition receptor for motile bacteria and fungi, TLR7 and TLR8, pattern recognition receptors for single-stranded RNA viruses, or TLR9, which is the pattern recognition receptor for bacterial DNA.…”
Section: Discussionsupporting
confidence: 79%
“…Blood outgrowth endothelial cells were grown out from progenitors in human blood as previously described ( 24 27 ). Once colonies emerged (between d 4 and 20), cells were expanded and maintained in Lonza EGM-2 medium (Lonza, Slough, United Kingdom) plus 10% fetal bovine serum, and experiments were performed between passages 2 and 8.…”
Section: Methodsmentioning
confidence: 99%
“…Reed et al [22] reported that human umbilical vein EC (HUVEC), blood outgrowth EC (BOEC), and iPSC-derived EC all displayed both toll-like receptor-4 (TLR4) and nucleotide-binding oligomerization domain-containing protein-1 (NOD1) molecules that are critical for sensing and binding gram negative bacterial organisms. In contrast, ESC-derived EC fail to express TRL4, but do bind and respond to gram negative bacteria via expressed NOD1.…”
Section: Studies With Human Esc or Ipscmentioning
confidence: 99%
“…Functional properties of hESC‐ECs derived in the presence and absence of SB43154, including endothelial permeability of confluent monolayers and tube formation abilities on two‐dimensional (2D) Matrigel and in three‐dimensional (3D) fibrin gels, were examined and compared. These properties were also compared with those of human umbilical vein endothelial cells (HUVECs), which have been widely used in studying angiogenesis and vasculogenesis in fibrin gels and used as a control for hPSC‐derived ECs . Striking differences in tube formation abilities of these three EC types have been found, suggesting that the phenotypes and functions of ECs derived from hPSCs under different conditions should be thoroughly studied prior to using these cells for translational studies and technology development.…”
Section: Introductionmentioning
confidence: 99%
“…These properties were also compared with those of human umbilical vein endothelial cells (HUVECs), which have been widely used in studying angiogenesis and vasculogenesis in fibrin gels and used as a control for hPSC-derived ECs. [24][25][26][27] Striking differences in tube formation abilities of these three EC types have been found, suggesting that the phenotypes and functions of ECs derived from hPSCs under different conditions should be thoroughly studied prior to using these cells for translational studies and technology development.…”
Section: Introductionmentioning
confidence: 99%